Ant Based Zonal Routing in Mobile Adhoc Networks - Singh, Gurpreet; Kaur, Amanpreet; Singh, Aashdeep; Gupta, Rohan (International Journal of Engineering and Technology, 2018)
Mobile Ad hoc network (MANET) is a collection of moving wireless nodes which form a temporary network topology without using any pre-existing network infrastructure. One of the challenges in MANET is to identify a path between the source and the destination nodes. MANET is highly deployable, self-organizing, autonomous and self-configuring network with the ability of rapid deployment. Nodes movement imposes high challenges to routing in MANET due to dynamically changing of topologies, low transmission power and asymmetric links. So well-organized routing is very critical task due to highly dynamic environment. Route instability occurs due to node mobility and leads to frequent change in topologies; therefore routing becomes one of the core issues. Many researchers are working on the expansion of routing protocols in MANET.Â